Impact of Covid-19 Second Wave Among Various Age Groups in South-Chennai: Life Sciences-Biochemistry - Kalai Selvi, V.S.; Mohamed Rabeek, Jainulavudeen; Shanthi, B.; Chandrika. A, Mary (International Journal of Life Science and Pharma Research, 2022)
India is under the second wave of the coronavirus disease (COVID-19). It seems that the second wave has created more impact than the first wave with an increased mortality rate. The mortality rate among young age group below 17 years is 0.05% with an increase of 16.6% above 17 years. Various studies have revealed that COVID-19 positive individuals show altered levels of both biochemical and hematological parameters with increased severity. To the best of our knowledge, no studies have investigated the altered levels with different age group. Hence, the study’s primary goal is to assess biochemical and haematological parameters in COVID-19 positive individuals and compare the levels in different age groups of the South Indian population in the second wave of COVID-19. The subjects were divided into 3 groups based on their age as between 19-40 years, 41-60 years, and 61-80 years. The biochemical parameters measured included liver and renal function tests, electrolytes, inflammatory markers, and blood glucose. ESR and haematological parameters were measured. Under biochemical parameters, serum urea, uric acid, and creatinine increased significantly with increasing age group, whereas serum albumin decreased significantly with increasing age group. With ferritin and CRP, there was statistical significance among different age groups. It was found that diabetic patients with high HbA1C levels with increase age are more prone to COVID-19 infection. On hematological investigation significant decrease in the eosinophil count and increased basophil count were observed among different age group. The study concludes that compared to younger age groups, older ones with COVID-19 showed increase in immune and inflammatory markers, Markers of the adaptive immune response also increased with age. Hence, continuous monitoring and additional care must be given the older ones to reduce the effects of severity of COVID-19 among south Indian population.